Constitutional and Legal Basis of Privatization and Denationalization of Property in the Republic of Belarus - Demichev, Dmitry Mikhailovich (Teisė, 2021)
The article examines the features of the constitutional and legal foundations of privatization and denationalization of property in the Republic of Belarus at the present stage.
Keywords: Constitution; State; President; Government; law; decree; economic relations; property; property right; reform; privatization; denationalization